2018
DOI: 10.1161/circheartfailure.117.004571
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-5 Is Elevated in Failing Single Ventricle Myocardium and Affects Cardiomyocyte Remodeling In Vitro

Abstract: Background: Single ventricle congenital heart disease (SV) is fatal without intervention and eventual heart failure (HF) is a major cause of morbidity and mortality. While there are no proven medical therapies for the treatment or prevention of HF in the SV population, phosphodiesterase-5 inhibitors (PDE5i), such as sildenafil, are increasingly utilized. While the pulmonary vasculature is the primary target of PDE5i therapy in patients with SV, the effects of PDE5i on the SV myocardium remain largely unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Interestingly, an increase in mitochondrial reserve and maximal capacity has also been reported in the platelets of adults with pulmonary hypertension ( 18 ), a common comorbidity in CHD patients. We noted a previous study that showed that serum from SV-CHD patients ( 5 ) can cause pathological remodeling with the reactivation of fetal gene programs in neonatal rat cardiomyocytes. The expression of HF markers, such as BNP ( 19 ) and atrial natriuretic factor ( 20 ) were observed, with transcriptome profiling showing metabolic process as one of the top enriched pathways.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, an increase in mitochondrial reserve and maximal capacity has also been reported in the platelets of adults with pulmonary hypertension ( 18 ), a common comorbidity in CHD patients. We noted a previous study that showed that serum from SV-CHD patients ( 5 ) can cause pathological remodeling with the reactivation of fetal gene programs in neonatal rat cardiomyocytes. The expression of HF markers, such as BNP ( 19 ) and atrial natriuretic factor ( 20 ) were observed, with transcriptome profiling showing metabolic process as one of the top enriched pathways.…”
Section: Discussionmentioning
confidence: 79%
“…Consistent with this, transcriptome profiling of the HLHS mouse heart tissue yielded metabolic pathways among the top pathways impacted ( 4 ). Supporting clinical evidence has come from a recent study showing that serum isolated from SV-CHD patients can induce pathological changes in neonatal rat cardiomyocytes ( 5 ). Transcriptome profiling of the treated cardiomyocytes showed that 23% of the genes impacted were related to metabolic processes ( 5 ).…”
Section: Introductionmentioning
confidence: 97%
“…Treatment with sera from patients with various cardiac diseases has been shown to induce changes in many different processes in cultured cells. Recently, Garcia et al showed that the treatment with single ventricle heart disease sera results in detrimental gene expression changes in cultured neonatal rat ventricular myocytes [ 29 ]. Furthermore, treatment with serum from heart failure (HF) patients or acute myocardial infraction (MI) has been shown to induce apoptosis and enhanced sprouting angiogenesis of cultured endothelial cells [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an interesting contrast in therapies such as phosphodiesterase inhibitors (PDEi) that have been found to be effective and safe in pediatric patients with heart failure but not as safe in adults (reviewed; Miyamoto et al, 2018 ). Moreover, PDE5i may be beneficial in improving RV function but it difficult to determine if this improvement is due to direct cardiomyocyte effects or simply improvement in pulmonary vascular function ( Nagendran et al, 2007 ; Garcia et al, 2018 ). It is not clear if PDEi are beneficial in RV function in adults.…”
Section: Right Ventricular Physiology In Adultsmentioning
confidence: 99%